(a²-b²-c²)-(b²-c²+a²)+(b²-a²)= a²-b²-c²-b²+c²-a²+b²-a²= (a²-a²-a²)-(b²+b²-b²)-(c²-c²)=(-a²)-(b²)-0= -a²-b²
-a²-b²≡-a²-b²
Автор:
floyd38(a² - b² - c²) - (b² - c² + a²) + (b² - a²) = - a² - b²
Раскроем скобки:
a² - b² - c² - b² + c² - a² + b² - a² = - a² - b²
Приведем подобные члены:
a² - b² - c² - b² + c² - a² + b² - a² = - a² - b²
- a² - b² = - a² - b²
Доказано.
Автор:
huffДобавить свой ответ
Предмет:
Английский языкАвтор:
lashonОтветов:
Смотреть
Предмет:
ХимияАвтор:
adolfoblankenshipОтветов:
Смотреть
Предмет:
Английский языкАвтор:
budsssfpОтветов:
Смотреть
Предмет:
МатематикаАвтор:
princesspma7Ответов:
Смотреть